A roadmap for optimizing chronic kidney disease patient care and patient-oriented research in the Eastern European nephrology community - Sever, Mehmet Şükrü; Jager, Kitty J; Vanholder, Raymond; Stengel, Benedicte; Harambat, Jerome; Finne, Patrik; Tesař, Vladimir; Barbullushi, Myftar; Bumblytė, Inga A; Zakharova, Elena; Spasovski, Goce; Resic, Halima; et al. (Clinical kidney journal, 2021)
Chronic kidney disease (CKD) is a major health problem because of its high prevalence, associated complications and high treatment costs. Several aspects of CKD differ significantly in the Eastern European nephrology community compared with Western Europe because of different geographic, socio-economic, infrastructure, cultural and educational features. The two most frequent aetiologies of CKD, DM and hypertension, and many other predisposing factors, are more frequent in the Eastern region, resulting in more prevalent CKD Stages 3-5. Interventions may minimize the potential drawbacks of the high prevalence of CKD in Eastern Europe, which include several options at various stages of the disease, such as raising public, medical personnel and healthcare authorities awareness; early detection by screening high-risk populations; preventing progression and CKD-related complications by training health professionals and patients; promoting transplantation or home dialysis as the preferred modality; disseminating and implementing guidelines and guided therapy and encouraging/supporting country-specific observational research as well as international collaborative projects. Specific ways to significantly impact CKD-related problems in every region of Europe through education, science and networking are collaboration with non-nephrology European societies who have a common interest in CKD and its associated complications, representation through an advisory role within nephrology via national nephrology societies, contributing to the training of local nephrologists and stimulating patient-oriented research. The latter is mandatory to identify country-specific kidney disease-related priorities. Active involvement of patients in this research via collaboration with the European Kidney Patient Federation or national patient federations is imperative to ensure that projects reflect specific patient needs.
Keywords: chronic renal failure; kidney transplantation; dialysis; ESRD; CKD